Operation of Single‐Spin Qubits: Recent Advances and Prospects - Zhizhuo Zhang; Jushang Ran; Fei Gao; Chuancheng Jia; Xuefeng Guo (Advanced Physics Research)
Abstract As a foundational technology in quantum information science (QIS), the manipulation and detection of quantum spins enable precise control, opening new avenues for significant advancements. Early research focused on macroscopic ensemble quantum systems, where electron spin resonance is used to coherently address electron spins within different ensembles. However, the low initialization efficiency and readout sensitivity of such systems hinder their further development. Unlocking the full potential of quantum technology, it is essential to achieve single‐spin precision. Various quantum systems, including color centers, quantum dots, atoms, and molecules, have been demonstrated the capability for single‐spin manipulation. The successful control of spin quantum states in these systems through diverse techniques has paved the way for new ideas and boundless possibilities in QIS. This review provides a comprehensive overview of recent significant advances in the field and explores future development directions, aiming to shed light on the ongoing evolution of QIS.